2017
DOI: 10.3889/oamjms.2017.160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Age on Average Dimensions of Arteries Forming the Circle of Willis Study by Magnetic Resonance Angiography on Kosovo’s Population

Abstract: BACKGROUND:Circulus arteriosus cerebri is the main source of blood supply to the brain; it connects the left and right hemispheres with anterior and posterior parts. Located at the interpenducular fossa at the base of the brain the circle of Willis is the most important source of collateral circulation in the presence of the disease in the carotid or vertebral artery.AIM:The purpose of the research is to study the diameter and length of arteries and provide an important source of reference on Kosovo’s populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…Our results indicate no difference between groups in ICA diameter. It is worth considering that males have larger cerebral (Müller et al, ; Shatri et al, ) and carotid arterial diameters (Krejza et al, ). Thus, we cannot discount the potential sex‐effect on vessel diameter despite matching the number of male ICA measures ( N = 3) in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate no difference between groups in ICA diameter. It is worth considering that males have larger cerebral (Müller et al, ; Shatri et al, ) and carotid arterial diameters (Krejza et al, ). Thus, we cannot discount the potential sex‐effect on vessel diameter despite matching the number of male ICA measures ( N = 3) in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal segment of anterior cerebral artery (A1) supplies the basal surface of the cerebral hemisphere. The diameter of A1 according to Kamath et al [10], 2.3 mm for diameter and 14.25 mm length, Iqbal et al [8] diameter 2.3 mm and length 12.4 mm, on Turkish population length of A1 is 14.4 mm [11] while diameter 1.58 mm in the right A1, 1.64 mm in the left A1 [18], in Kosovo's population the diameters of A1 was 2.09 mm while length 13.96 mm [16]. In our study the diameter of ACA was 2.05 and length 14.01 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke survivors face long-term disability and cognitive deficits ( 37 ). Previous studies demonstrated that females have smaller MCA compared with males in humans ( 45 , 51 , 64 ) and in rats ( 61 ). The MCA in females has greater responses to hypercapnia, nitric oxide (NO), and flow-mediated vasodilation ( 31 , 47 , 54 , 56 ) and lower responses to angiotensin II (ANG II) as well as endothelin-1 (ET-1)-induced vasoconstriction ( 1 , 62 ).…”
Section: Introductionmentioning
confidence: 96%